PENGUKURAN, SOSIALISASI GEJALA DAN PENANGANAN DINI HIPERTENSI PADA LANSIA DI KECAMATAN LEUWIGOONG KABUPATEN GARUT - Tantri Puspita; Sri Yekti Widadi; Muhammad Hadi Sulhan (LP4M STIKes Karsa Husada Garut, 2021)
Hypertension is better known by the public as a disease of high blood pressure. High blood pressure (High Blood Pressure / BP), diabetes mellitus and lipid abnormalities are the most common risk factors for cardiovascular disease. The implementation method used is blood pressure checks and counseling related to hypertension. The location of this health education is Lewigoong-Garut District, precisely in Kampung. Ciseureuh Village. Sindangsari. The target of this health education is the pre-elderly-elderly age range. The purpose of conducting health examinations and counseling on blood pressure in Leuwigoong District, Garut Regency are: Knowing the blood pressure in the community and the possibility of hypertension they are experiencing, Increasing public knowledge about the dangers and complications of hypertension, Providing knowledge of general and specific symptoms when blood pressure is above normal/ Hypertension, Providing knowledge about early treatment of Hypertension, Disseminating a healthy lifestyle to young and old age for the prevention of Hypertension. From this community service activity, it can be concluded that blood pressure checks are very useful for residents of Cisereuh Leuwigoong village. Examination that coincides with hypertension education to residents on a one by one basis is more effective when compared to the lecture method because the examiner and residents directly interact and communicate directly.